Hubungan indeks massa tubuh dengan FEV1/FVC pada mahasiswa Fakultas Kedokteran Angkatan 2023 Universitas Sam Ratulangi Manado - Kindangen, Fiorenza; Pangemanan, Damajanty Helen Carol; Pangkahila, Erwin Adams (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Background: Body mass index (BMI) is a simple anthropometric measurement by measuring height and weight to determine a person's nutritional status. Pulmonary function test is one way that can be done to measure FEV1 (Forced Expiratory Volume 1 Second)/FVC (Forced Vital Capacity), namely by using spirometer as a tool to measure lung function. Lung function can decrease as BMI increases. In the parameters of lung function, there is an abnormal lung volume of respiratory efficiency in people who are obese. Aim: To determine the relationship between BMI and FEV1/FVC in Unsrat Faculty of Medicine students batch 2023. Methods: Analytical research type with cross-sectional study design with purposive sampling technique measuring height and weight to calculate BMI and measuring FEV1/FVC using a spirometer data analysis using the spearman rho test. Results: BMI less as many as 6 people (7.1%), normal BMI amounted to 41 people (48.8%), BMI more / overweight amounted to 14 people (16.7%), BMI obesity 1 as many as 18 people (21.4%) and BMI obesity II as many as 5 students (6.0%). There were 80 people (95.2%) who had normal FEV1/FVC values, for mild FEV1/FVC values there were 3 students (3.5%), and for moderate FEV1/FVC values there were 1 student (1.2%). The results of the Spearman correlation test significance value p=0.120, which means H0 is accepted and H1 is rejected. Conclusion: There is no relationship between BMI and FEV1/FVC in students of the Faculty of Medicine Batch 2023, Sam Ratulangi University Manado. Keywords: body mass index, FEV1/FVC